The Unfolding of the Royal Status of Jesus: A Narrative Study of John 19.16b–24 - LoboSJ, Rayan Joel (The expository times, 2025)
This article presents a narrative analysis of John 19:16b–24, exploring how the crucifixion pericope reveals the royal status of Jesus in the Fourth Gospel. Structured in three main sections—delimitation, plot analysis, and character studies—the study offers a close reading of the text that highlights its literary coherence and theological depth. The narrative is shown to be intricately shaped to unveil Jesus’ kingship, even in the apparent humiliation of the cross. Intertextual connections with the Last Supper scene and the Old Testament story of Joseph enrich the portrayal, emphasizing themes of sovereignty, divine purpose, and irony. Through the lens of narrative criticism, the article argues that this pericope, far from depicting defeat, serves as a climactic revelation of Jesus’ royal identity—enthroned not despite the cross, but precisely through it.